2016
DOI: 10.1186/s12913-016-1307-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting health services use among older people in China: An analysis of the China Health and Retirement Longitudinal Study 2013

Abstract: BackgroundRapid population ageing in China is increasing the numbers of older people who are likely to require health services in response to higher levels of poor perceived health and chronic diseases. Understanding factors influencing health services use at late life will help to plan for increasing needs for health care, reducing inequalities in health services use and releasing severe pressures on a highly variable health care system that has constrained public resources and increasing reliance on health i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
186
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(220 citation statements)
references
References 33 publications
26
186
1
7
Order By: Relevance
“…Despite an association between age and healthcare use in this study which is consistent with previous studies [30][31][32][33], the finding that respondents aged between 85 and 89 years were significantly less likely to use healthcare was counter-intuitive and appeared inconsistent with our expectation and earlier studies in LMICs. This is because, a study in 16 European countries revealed that the propensity of having multimorbidities increased considerably with advancing age [34].…”
Section: Discussionsupporting
confidence: 52%
“…Despite an association between age and healthcare use in this study which is consistent with previous studies [30][31][32][33], the finding that respondents aged between 85 and 89 years were significantly less likely to use healthcare was counter-intuitive and appeared inconsistent with our expectation and earlier studies in LMICs. This is because, a study in 16 European countries revealed that the propensity of having multimorbidities increased considerably with advancing age [34].…”
Section: Discussionsupporting
confidence: 52%
“…There are inconsistent reports about the influence of residence even for total healthcare utilization (private, public and others combined). Some studies highlighted that urban residents are more likely to use healthcare than rural counterparts [16,39], whereas another study in China reported that healthcare utilization has been increased among rural respondents compared to urban residents [40]. Some others have shown that no significant association exists between residence (urban/rural) and healthcare utilization [15,41].…”
Section: Discussionmentioning
confidence: 99%
“…Relative living standard was assessed by responses to the question "Compared to the average living standard of people in your city or county, how would you rate your standard of living?" 2 Response options were much better, a little better, about the same, a little worse, much worse, collapsed into three categories corresponding to better, same, and worse [40]. Worse than the average relative living standard is treated as having financial strain/uncertainty.…”
Section: Methodsmentioning
confidence: 99%
“…Worse than the average relative living standard is treated as having financial strain/uncertainty. Urban and rural residency was determined by the most recently published statistical standard by the Chinese National Bureau of Statistics based on an area's social and economic development [40].…”
Section: Methodsmentioning
confidence: 99%